Academic Senate Minutes 2009-10-01 - Academic Senate:::::::::
Agenda Approved. Minutes of 9/30/09 Approved. Chair Report. Update on WASC. Statewide Senators Report. President Report. Associated Students Report. By-Laws Revision: Change to Charge of Structure and Functions amended and approved. Provost Report. Vice President of SAEM Report. EPC Report. Senate Budget Committee Report. Report from the Ad-Hoc Diversity Committee. Resolution recognizing the work of the Senate's Ad-Hoc Diversity Committee offered from the floor – First Reading.